Karst Aquifer in Mt Galicica and Possibilites for Water Supply to Ohrid with Ground Water (Geologica Macedonica, 2013)
In this paper are presented some hydrogeological features of the karst aquifer in Mt Galičica, which contains important quantities of ground-water that can to used for the water supply of the town Ohrid. Based on the hydrogeological data are given three solutions that be can to used for water suply of Ohrid, the first one is to drill of deep wells, combination of deep and shallow wells, as well as construction of horizontal galleries.